2008
DOI: 10.1508/cytologia.73.437
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Studies of Metal Ion Tolerance in the Red Algae <i>Cyanidioschyzon merolae</i>

Abstract: SummaryThe unicellular red alga Cyanidioschyzon merolae is tolerant of high levels of several different metal ions. Cells of the alga cultured with divalent or trivalent metal ions at 10 mM contained elevated concentrations of each metal. The highest tolerance was shown for Al followed by Fe, CuϾNiϾZnϾMn. The viability and morphology of the cells were investigated for different periods of time after metal addition. In contrast to land plants, C. merolae exhibited a very high tolerance to metal ions, but the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…2) confirming the long-term metabolic adaptability of C. merolae to such high Ni concentrations. The cell survivability data is in contrast with the work by Misumi et al, (2008) who observed up to 20% viability of C. merolae cells upon 10 mM Ni treatment on day 70, measured as autofluorescence of the chloroplast. In the latter work, the experimental and culture conditions were considerably different, as a different Ni source was used (Ni(NO 3 ) 2 instead of NiSO 4 ); growth pH was slightly lower (2.3 compared to 2.5 in this work) and the final cell suspension volume was also different (50 versus 125 mL in this work), all of which may affect the effective toxicity of Ni in the cells.…”
Section: Growth and Viability Of C Merolae Cells In Presence Of High ...contrasting
confidence: 99%
See 2 more Smart Citations
“…2) confirming the long-term metabolic adaptability of C. merolae to such high Ni concentrations. The cell survivability data is in contrast with the work by Misumi et al, (2008) who observed up to 20% viability of C. merolae cells upon 10 mM Ni treatment on day 70, measured as autofluorescence of the chloroplast. In the latter work, the experimental and culture conditions were considerably different, as a different Ni source was used (Ni(NO 3 ) 2 instead of NiSO 4 ); growth pH was slightly lower (2.3 compared to 2.5 in this work) and the final cell suspension volume was also different (50 versus 125 mL in this work), all of which may affect the effective toxicity of Ni in the cells.…”
Section: Growth and Viability Of C Merolae Cells In Presence Of High ...contrasting
confidence: 99%
“…In the latter work, the experimental and culture conditions were considerably different, as a different Ni source was used (Ni(NO 3 ) 2 instead of NiSO 4 ); growth pH was slightly lower (2.3 compared to 2.5 in this work) and the final cell suspension volume was also different (50 versus 125 mL in this work), all of which may affect the effective toxicity of Ni in the cells. Moreover, in Misumi et al, (2008), the starting OD of the culture is not specified. In the present study, the starting OD 750 was ∼0.150 at 750 nm, which could have caused much higher total effective toxicity of Ni compared to the work by Misumi and colleagues (2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cyanidiophyceae, one of seven red algal classes, contains well-known extremophiles. Most species occur in environments with high temperatures (45-65°C) and acidic environments (pH 0.5-3.0), and they are sometimes found where there are high concentrations of heavy metals (Beardall & Entwisle, 1984;Enami et al, 2010;Minoda et al, 2015;Misumi et al, 2008;Nagasaka et al, 2002Nagasaka et al, , 2004. Therefore, Cyanidiophyceae occur worldwide in diverse volcanic sites, hot springs, hydrothermal pits, mines, and acidic swamps (Barcyte et al, 2018;Ciniglia et al, 2004;Toplin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Cyanidiophyceae are tolerant to heavy metals and absorb high concentrations of them from an aquatic environment (Nagasaka et al, 2004; Misumi et al, 2008). This is because metals are easily ionized and dissolved in acidic water.…”
Section: Introductionmentioning
confidence: 99%